1986
DOI: 10.1037/0735-7044.100.3.343
|View full text |Cite
|
Sign up to set email alerts
|

Processing of preconsciously acquired information measured by hemispheric asymmetry and selection accuracy.

Abstract: This study was conducted to investigate the effects of instruction types on hemispheric activation and accurate selection of spatial stimuli that had been previously presented at a subliminal level. Right-handed females randomly received either an "analytic" or a "holistic" instruction. Both groups first saw a series of slides for an extremely brief time (1 ms). Subsequently, these slides were paired with similar but novel slides. One group was asked to view the pairs analytically and to select the one they th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In many instances, liking for neutral stimuli increased as a function of a small number of previous exposures yet perceivers could not consciously recognise the previously exposed stimuli (Barchas & Perlaki, 1986;Bonanno & Stillings, 1986;Bornstein et al, 1987;Kunst-Wilson & Zajonc, 1980;Mandler et al, 1987;Murphy et al, 1995;Seamon et al, 1983Seamon et al, , 1984Seamon et al, , 1995Thompson et al, 2000). Processing fluency provides an elegant account of these response patterns and of the 232 SCHELLENBERG, PERETZ, VIEILLARD independence between implicit memory (as evidenced by increases in liking) and explicit memory.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In many instances, liking for neutral stimuli increased as a function of a small number of previous exposures yet perceivers could not consciously recognise the previously exposed stimuli (Barchas & Perlaki, 1986;Bonanno & Stillings, 1986;Bornstein et al, 1987;Kunst-Wilson & Zajonc, 1980;Mandler et al, 1987;Murphy et al, 1995;Seamon et al, 1983Seamon et al, , 1984Seamon et al, , 1995Thompson et al, 2000). Processing fluency provides an elegant account of these response patterns and of the 232 SCHELLENBERG, PERETZ, VIEILLARD independence between implicit memory (as evidenced by increases in liking) and explicit memory.…”
Section: Discussionmentioning
confidence: 92%
“…Focused exposure leads to accurate recognition but not to increases in liking, whereas incidental exposure leads to increases in liking in the absence of explicit memory (Szpunar et al, 2004, Experiment 1). In fact, there is abundant empirical evidence of liking in the absence of explicit memory for impoverished and neutral stimuli presented in either visual or auditory modalities (Barchas & Perlaki, 1986;Bonanno & Stillings, 1986;Bornstein, Leone, & Galley, 1987;Kunst-Wilson & Zajonc, 1980;Mandler, Nakamura, & Van Zandt, 1987;Murphy, Monahan, & Zajonc, 1995;Seamon, Brody, & Kauff, 1983;Seamon, Marsh, & Brody, 1984;Seamon et al, 1995;Thompson et al, 2000). When the stimuli are rich and aesthetically pleasing, however, the twofactor model appears to provide a better account of response patterns.…”
mentioning
confidence: 86%
“…Vigilance versus learning mode of receipt of stimuli (Barchas and Perlaki 1986;Dimond and Beaumont 1973);…”
Section: Voluntary Versus Involuntarymentioning
confidence: 99%
“…Literature reviews on EEG hemispheric specificity show that, on the whole, studies have focused on research of reactions to afferent stimulation or of performance of psychological tasks. Furthermore, these studies have been carried out primarily on right-handed subjects (Barchas & Perlaki, 1986;Beaumont, Mayes, & Rugg, 1978). The importance of taking functional asymmetry into account in the research of EEG hemisphere specificity is confirmed by clinical data of the differences in psychoneurological symptoms of focal brain damage in left-and right-handed subjects (Dobrokhotova & Bragina, 1977).…”
Section: Study Of Healthy Participantsmentioning
confidence: 99%